Viewpoint: A Viewpoint on COP 15- Dispatches from Copenhagen - Million Belay (Environmental Association of Southern Africa, 2009)
These dispatches from Copenhagen were received from Million Belay, director of an environmental non-governmental organisation (NGO) in Ethiopia called MELCA. Million is a well-known environmental activist and educator in Africa, with long-standing contributions to conservation in Africa. He is currently completing a PhD on biocultural diversity, community learning and agency. Since this edition of the SAJEE takes its theme as 'Environmental Education in the Year of COP 15', I thought it would be of interest to EEASA members if we published some of the 'coalface' experiences of a respected environmental education researcher and activist who attended KlimaForum09 (the main civil society gathering at COP 15). The dispatches cover 10 days' participation at COP 15 and are collected here as Copenhagen 1-10. They give insight into the range and complexity of the issues being discussed, the socio-politics of the time and how participation happens in such events. For education, it is perhaps salient to develop a deeper understanding of the social processes that shape how and what we educate about (e.g. climate change issues, REDD) and Million leaves us with some profound questions to ponder.